State Responsibility for the Protection of the Cultural Heritage During Wartime Before the International Court of Justice (ICJ) - Baroudy, Jinane El; Albakjaji, Mohamad (Journal of Posthumanism, 2025)
Armed conflict against any state can result in devastating consequences—not only for human lives but also for the preservation of cultural property. Such conflicts often lead to the destruction of monuments, the erasure of cultural identities, and, in some cases, the obliteration of entire cultural groups. This paper examines the role of the International Court of Justice (ICJ) in the protection of cultural heritage. It begins by outlining the sources and legal status of international obligations related to cultural heritage during armed conflict, with reference to key international instruments. The analysis then turns to the ICJ’s evolving jurisprudence on cultural heritage, highlighting how the Court interprets existing legal frameworks and contributes to the development of customary international law in this area. Furthermore, the paper discusses the consequences of violations of these obligations and critically assesses the limitations of international law in offering comprehensive protection. It also considers the challenges in establishing State responsibility for breaches of cultural heritage obligations, particularly with respect to attributing wrongful conduct to a specific State.